Awareness of internet banking / Wan Mohamad Nidtzar Wan Mohd Nadziham - Wan Mohd Nadziham, Wan Mohamad Nidtzar (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
This study aims to measure the level of awareness in Internet Banking. This study will focused only amongst students in Muamalat and Halal Management in UiTM Puncak Alam. Internet Banking has become a tool that ease many people in this world. The purpose of study is to obtain data on the usage of Internet Banking among student Uitm Puncak Alam. Quantitative method has been used in performing this study. For instance, a survey using 5 point Likert scales questionnaire will be used to collect the data. There were 66 respondents that will completely returned the questionnaire which were used for computing the scores and data analysis. Then, this study will reveals the level of awareness in Internet Banking amongst respondents whether it will be in high level, moderate or low. This study has three aims. The first aim is to identify types of transaction that used by customer and analyze how they solve the problem in this service. Secondly, to identify among UiTM Puncak Alam students about Internet Banking. Thirdly, to study the usage frequency of internet banking among UiTM Puncak Alam students and finally to investigate the satisfaction of using internet banking among UiTM Puncak Alam students and how to improve the weaknesses of this usage . Main finding of this study, is to investigate the awareness of internet banking among Uitm Puncak Alam. It is also benefit to university especially faculty because it can be the one of references that can be used in the next generation. It can be applied in the study that related to internet banking. This research also can lead students to understanding the concept of internet banking and more topics that includes in this research. In order to fulfill the requirement by Faculty of Academy Contemporary Islamic Studies, Universiti Teknologi Mara, Campus Puncak Alam, the investigation and research also help researcher improve the knowledge about banking especially in internet banking system. Besides, it also can make researcher gain more knowledge not just in theory but also in the real practice. It will be essential while researcher going to work. Teenagers and youngsters are likely to spend more using internet banking than the old folks. This is because, the scope of study shows that internet banking is a trend to the youngsters.